KEPEMIMPINAN DISTRIBUTIF SEBAGAI STRATEGI PENINGKATAN MUTU SDM PENDIDIKAN ISLAM - Agus Karjuni; Abdurrahman Afif Suza (Universitas Islam Bunga Bangsa Cirebon, 2024)
Background Human resource quality in Islamic educational institutions remains a persistent challenge, partly due to leadership models that concentrate authority in single figures, thereby limiting the professional growth of educators and staff. Objective This study aims to examine the concept of distributive leadership as a strategic approach to enhancing human resource quality in Islamic educational institutions and to formulate an integrative model grounded in Islamic values. Methodology A library research methodology was employed, utilizing authoritative books and reputable journal articles published within the last five years. Data were gathered through systematic documentation and subjected to content analysis combined with referential adequacy testing. Results Findings demonstrate that distributive leadership fosters collective professional capacity, distributes responsibility equitably, cultivates a culture of continuous learning, and accelerates organizational competence development when integrated with Islamic management values.